Optimal response to tislelizumab plus chemotherapy in metastatic triple-negative breast cancer: a case report and literature review - Ma, Yuxin; Shi, Xinhong; Zhao, Kun; Hu, Shuyi; Shi, Yue; Jiang, Yingying; Liu, Yiling; Lu, Lin; Chang, Yuting; Zhou, Fei; Dai, Yingying; Wu, Zipeng; et al. (Frontiers in Oncology, 2024)
Metastatic triple-negative breast cancer (mTNBC) is one of the worst prognosis breast cancer.Immune checkpoint inhibitors (ICIs) plus chemotherapy gets promising survival benefits. Herein, we report a 51-year-old woman whose metastatic lesions were diagnosed as triple-negative subtype, received tislelizumab plus eribulin treatment and achieved excellent efficacy. To our best knowledge, this study is the first attempt to present tislelizumab in combination with eribulin in mTNBC. New treatments resulting in prolonged survival and durable clinical responses would benefit mTNBC patients and then we summarize the possible influencing factors of the interaction between tislelizumab and eribulin.